CONTEXT DEPENDENT SENSORY PROCESSING ACROSS PRIMARY AND SECONDARY SOMATOSENSORY CORTEX - Condylis, Cameron (Neuron, 2020)
To interpret the environment, our brain must evaluate external stimuli against internal representations from past experiences. How primary (S1) and secondary (S2) somatosensory cortices process stimuli depending on recent experiences is unclear. Using simultaneous multi-area population imaging of projection neurons and focal optogenetic inactivation, we studied mice performing a whisker-based working memory task. We find that activity reflecting current stimulus, the recollection of previous stimulus (cued recall), and stimulus category are distributed across S1 and S2. Despite this overlapping representation, S2 is important for processing cued recall responses and transmitting this to S1. S2 network properties differ from S1, wherein S2 persistently encodes cued recall and stimulus category under passive conditions. While both areas encode stimulus category, only information in S1 is important for task performance through pathways that do not necessarily include S2. These findings reveal both distributed and segregated roles for S1 and S2 in context-dependent sensory processing.